Does Personality Influence Ego Depletion dan Self Regulation for Children’s With Special Need Teacher ? - Undarwati, Anna (Indonesian Journal of Early Childhood Education Studies, 2016)
The psychological aspects of teacher whom educate children’s with special needs are rarely discussed. As teacher has complex tasks in managing the learning pro- cess, it is predicted that teacher‘s energy is more exhausted than teacher for normal children. This research has two purposes, first to distinguish the ego depletion at teachers with observing personality types. Second, to differentiate teacher’s selfregulation in with observing personality types. The research method used quantitative comparative approach. Participants in this research were teachers who work in public school for students with special needs in Semarang and Ungaran city. Participants were employed ego depletion scale, scale of self-regulation, and introverted-extroverted personality type-scale. The result showed that t = -0.917 (p> 0.05), which means there was no difference between ego depletion with measuring personality type (introvert and extrovert) of teachers. Subsequent analysis was known that score t = -0.032 (p> 0.975), it means that there was no difference between selfregulation and personality type (extrovert and introvert) of teachers. It can be concluded that personality type (extrovert-introvert) doesn’t influence individual’s ego depletion. Likewise, the self-regulation also doesn’t affected by the personality type.